The influenza season 2016/17 in Bucharest, Romania – surveillance data and clinical characteristics of patients with influenza-like illness admitted to a tertiary infectious diseases hospital - Drăgănescu,Anca (2018)
ABSTRACT Background: Influenza continues to drive seasonal morbidity, particularly in settings with low vaccine coverage. Objectives: To describe the influenza cases and viral circulation among hospitalized patients. Methods: A prospective study based on active surveillance of inpatients with influenza-like illness from a tertiary hospital in Bucharest, Romania, in the season 2016/17. Results: A total of 446 patients were tested, with a balanced gender distribution. Overall, 192 (43%) patients tested positive for influenza, with the highest positivity rate in the age groups 3–13 years and >65 years. Peak activity occurred between weeks 1 and 16/2017, with biphasic distribution: A viruses were replaced by B viruses from week 9/2017; B viruses predominated (66.1%). Among the 133 (69.3%) subtyped samples, all influenza A were subtype H3 (n = 57) and all influenza B were B/Victoria (n = 76). Patients who tested positive for influenza presented fewer comorbidities (p = 0.012), except for the elderly, in whom influenza was more common in patients with comorbidities (p = 0.050). Disease evolution was generally favorable under antiviral treatment. The length of hospital stay was slightly longer in patients with influenza-like illness who tested patients negative for influenza (p = 0.031). Conclusions: Distinctive co-circulation of A/H3 and B/Victoria in Bucharest, Romania in the 2016/17 influenza season was found. While the A/H3 subtype was predominant throughout Europe that season, B/Victoria appears to have circulated specifically in Romania and the Eastern European region, predominantly affecting preschoolers and school children.